(untitled) (Journal of KIST Medical College, 2020)
Introduction: Pediatric injury is one of the common emergencies encountered in the emergency department. It is emerging as leading cause of death and disabilities in children. This study aims to analyze the patterns of pediatric injury based on age group, gender, mode, type, place of injury and its outcome. Methods: This is a descriptive cross sectional study conducted in Emergency Department of KIST Medical College and Teaching Hospital from 1st May 2019 to 30th July 2019. A total of 110 patients aged 15 years and below and with history of trauma were included in this study. Results: A hundred and ten pediatric patients presented to emergency with injuries. Majority of pediatric trauma cases belonged to age group 1-5 years (38.2%, n=42) and more frequent in male children (66.4%, n=73) .In both gender, male (45.5%, n=50) and female (17.3%, n=19); fall was most common mode of injury followed by accidental cut injury (7.3%,n=8) in male and road traffic accident (6.4%,n=7) in female. Most of the cases sustained soft tissue injury (32.7%, n=36) followed by cut injury (26.4%, n=29) and fracture (16.4%, n=18). Common place of injury was found to be at home (64.5%, n=71). Majority were discharged (n=100; 90.9%), Nine (8.2 %) were admitted and one expired (0.9 %) expired. Conclusion: Fall injuries are the major mode of injury encountered in both male and female children. Injuries tend to occur more at home than school. Children should be adequately supervised at home and school.